2019
DOI: 10.1186/s40608-019-0231-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized home-based childhood obesity prevention pilot intervention has favourable effects on parental body composition: preliminary evidence from the Guelph Family Health Study

Abstract: Background Home-based lifestyle behaviour interventions show promise for treating and preventing childhood obesity. According to family theories, engaging the entire family unit, including parents, to change their family behaviour and dynamics may be necessary to prevent the development of childhood obesity. However, little is known about how these interventions, which may change the family dynamics and weight-related behaviours of parents, affect weight outcomes in parents. Our objective was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…The program may have encouraged families to implement more structured, organized behavioural patterns focused around these health goals, thus calming the home environment and increasing parenting confidence; however it is also possible that the program may have caused conflict or confusion from the disruptions to the families' typical behaviours. Our results suggest that family stress levels were not different when comparing intervention to control families, despite evidence that behavioural changes did indeed occur among both parents and children [27,36,37].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The program may have encouraged families to implement more structured, organized behavioural patterns focused around these health goals, thus calming the home environment and increasing parenting confidence; however it is also possible that the program may have caused conflict or confusion from the disruptions to the families' typical behaviours. Our results suggest that family stress levels were not different when comparing intervention to control families, despite evidence that behavioural changes did indeed occur among both parents and children [27,36,37].…”
Section: Discussioncontrasting
confidence: 52%
“…The GFHS pilot studies demonstrated success in increasing children's fruit and vegetable consumption [36] and at post-intervention, children and parents had lower indices of body fat [27,37]. This suggests that the GFHS intervention program did meaningfully change some family behaviours, but until the present study, it was unknown how these changes could impact families' stress levels.…”
Section: Discussionmentioning
confidence: 65%
“…Family-based multi-component weight loss behavioral treatment is the gold standard for treating childhood obesity, and it is having been found useful in those between 2 and 6 years old ( 150 , 159 ). Additionally, empowering the parents to play an equal role in developing and implementing an intervention for weight management has shown promising results in improving the rate of obesity by decreasing screen time, promoting healthy eating, and increasing support for children's physical activity ( 160 , 161 ).…”
Section: Treatmentmentioning
confidence: 99%
“…It is because of mutation of the ATP7B gene that leads to dysfunction of the copper-transported enzyme P-kind ATPase [28], this enzyme is liable for transported copper into bile and incorporating it into ceruloplasmin [25]. The protein is synthesized by the liver and is the foremost copper provider in the blood [29,30]. A discount of ceruloplasmin in the plasma is a sign of WD [23].…”
Section: Wilson's Disordermentioning
confidence: 99%
“…Celiac disorder celiac disease may be associated with hypertransaminasemia and fatty liver disease "Celiac hepatitis'' is the utmost common place hepatopathy in those tolerant and is depict through slightest and non-precise histological liver lesions [6]. These deals are commonly reversible after just a few months following the start of a gluten-free diet in cases of fatty liver which are not responsive to a gluten-unfastened food plan it's far important to exclude different causes of liver damage [35], inclusive of obesity and other illness affecting the liver, such as autoimmune hepatitis, autoimmune cholangitis, and overlap syndrome [30].…”
Section: Gastrointestinal and Nutrition Diseasesmentioning
confidence: 99%